2008
DOI: 10.4314/sjms.v3i3.38540
|View full text |Cite
|
Sign up to set email alerts
|

The Pattern Of Neurological Manifestations Of Tuberculosis Among Adult Sudanese Patients

Abstract: Objective: To study the pattern of neurological manifestations of tuberculosis among adult Sudanese tuberculous patients seen at El-Shaab Teaching Hospital (Sudan). Methods: This study was performed on 179 Sudanese patients with tuberculosis admitted at El-Shaab Teaching Hospital during the period from May 2005 to January 2006. Demographic and clinical data were obtained. Investigations including CXR, sputum for acid alcohol fast bacilli [AAFB], Mantoux test, complete haemogram were done. Screening for HIV, NC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
2
1
0
Order By: Relevance
“…In this study, Pott's disease was found in 29 (67.4%), brain tuberculoma in 8 (18.7%), and TB meningitis in (13.9%). Similar to our study, the study by Hussein et al 13 reported Pott's paraplegia in 22 out 57, tuberculoma in 6, and TB meningitis in 3.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, Pott's disease was found in 29 (67.4%), brain tuberculoma in 8 (18.7%), and TB meningitis in (13.9%). Similar to our study, the study by Hussein et al 13 reported Pott's paraplegia in 22 out 57, tuberculoma in 6, and TB meningitis in 3.…”
Section: Discussionsupporting
confidence: 92%
“…Extraneural tuberculosis was found in six patients, and CSF and PCR were found positive in seven out of nine patients; three patients died, five recovered with residual weakness, and two recovered completely. Similar findings were reported by Hussein et al, 13 who stated that 22 patients presented with Pott's paraplegia, 18 with peripheral neuropathy, 6 had tuberculoma, 3 had quadriplegia, 3 with tuberculous meningitis, 2 had proximal myopathy, 2 had hemiplegia, and 1 had multiple cranial nerves palsies.…”
Section: Discussionsupporting
confidence: 88%
“…Very little has been documented about the disease in Sudan, though high endemicity of tuberculosis in some regions of the country. Few studies on clinical presentation and complications of the disease were published 7,8 . The aim of this study is to define the most affected vertebral region of the spine in Sudanese patients with Potts disease.…”
Section: Introductionmentioning
confidence: 99%